Evaluation of antispermatogenic and antifertility properties of Terminalia chebula (Retz.) in albino mice - Gupta, Prakash Chandra; Yadav, Laxmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: The development of an orally active, safe, reversible, and effective male contraceptive of plant origin has always been a matter of great interest among researchers due to its ready availability, cost-effectiveness, and most importantly protection of privacy. The present study was conducted to evaluate the effect of oral feeding of Terminalia chebula Retz. (T. chebula; family: Combretaceae) on male reproductive organs and fertility. Methods: The albino mice were administered orally acetone, methanol, 50% ethanol, and aqueous bark extracts of T. chebula (300 mg/kg body weight daily) for 35 days, and the effect of the treatments on testis, epididymis, seminal vesicle, sperm parameters, biochemical, and fertility indices was investigated. Toxicological studies were also carried out. Results: Treatment with Terminalia extracts brought non-uniform but detectable histologic alterations in the testis, epididymis, and seminal vesicle; the alterations caused in the reproductive organs were, however, severe in mice treated with the aqueous extract of Terminalia compared to those in other treated groups and controls. Further, the level of fructose in the seminal vesicle and that of sialic acid in the epididymis reduced significantly in the above treated mice. Sperm parameters were adversely affected in extracts-treated mice. Libido was not affected, but fertility reduced significantly in aqueous extract-treated males as compared to controls. Further, histoarchitecture of the liver and kidney, serum levels of ALT, AST, creatinine, and haematological parameters remained unaltered in Terminalia-treated mice compared to controls. Conclusions: The results of the present study, therefore, suggested that the aqueous bark extract of T. chebula causes suppression of spermatogenesis and fertility in albino mice, and therefore, might be valuable in male fertility regulation.